Pengaruh lokasi usaha dan jam kerja terhadap pendapatan pedagang pasar panorama kota Bengkulu - pakri Fahmi (Universitas Prof.Hazairin,SH Bengkulu, 2021)
This study aims to examine the effect of business location and working hours on the income of traders of the Bengkulu city panorama market. This research was conducted in the Bengkulu city panorama market. The number of samples in this study was 100 respondents. The results showed that 35.6% of the variables of business location and working hours were able to explain the income variable of the panoramic market traders of Bengkulu City. Based on the results of the simultaneous test, the variable of business location and working hours affect the income of traders of the Bengkulu panoramic market, while based on the Partial test, the variable of business location affects the income of traders of the Bengkulu city panorama market, but working hours have no effect on the income of traders of the Bengkulu city panorama market.